SANTRIPRENEURSHIP: INTERNALIZING THE VALUES OF INDEPENDENCE IN THE DIGITAL ERA (CASE OF PONDOK PESANTREN IN MALANG RAYA) - Iva Khoiril Mala; Heri Pratikto; Agung Winarno (Indonesian Journal of Business and Entrepreneurship (IJBE), 2020)
This study aimed to reveal the process of internalizing the self-reliance values of santri in the digital era at pondok pesantren Malang Raya, East Java. The approach of this study was descriptive and qualitative. The data were collected through in-depth interviews and observations with the respondents consisting of three kiai, five board of pondok pesantren, three teachers, and eight students. The data analysis used a simultaneous stage model consisting of approach, extracting, deepening, matching, interpretation, and presentation. The results showed that the character values implanted were the values of independence, namely not depending on others and not oriented to the company/employee organization. The value cultivation system was carried out using the kiai's teachings through learning based on the available ulama books and practical assignments to assist trading businesses, product processing, and services in pondok pesantren's cooperative. Utilization and understanding of the use of internet technology is very appropriate in the context of reducing the character ordering morality. Keywords: digital era, obedience to kiai, santri, values of independence